2020
DOI: 10.3389/fmed.2020.00493
|View full text |Cite
|
Sign up to set email alerts
|

Education and Message Framing Increase Willingness to Undergo Research Lumbar Puncture: A Randomized Controlled Trial

Abstract: Reluctance to undergo lumbar puncture (LP) is a barrier to neurological disease biomarker research. We assessed whether an educational intervention increased willingness to consider research LP and whether message framing modified intervention effectiveness. We randomly assigned 851 recruitment registry enrollees who had previously indicated they were unwilling to be contacted about studies requiring LP to gain or loss framed video educational interventions describing the procedure and the probability of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Consistent with our results, an RCT of screening of undiagnosed atrial fibrillation that used behavioral nudges under multiple forms, including personalization, managed to increase enrollment rates from 0.8% to 9.4% over 10 months [6]. Similarly, Witbracht et al [7] found that message framing was effective in changing subjects' initial negative response to undergo research lumbar puncture, with participants randomized to the gain framed intervention having 67% higher odds of agreeing to be contacted about studies requiring lumbar puncture compared to those randomized to the loss frame.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with our results, an RCT of screening of undiagnosed atrial fibrillation that used behavioral nudges under multiple forms, including personalization, managed to increase enrollment rates from 0.8% to 9.4% over 10 months [6]. Similarly, Witbracht et al [7] found that message framing was effective in changing subjects' initial negative response to undergo research lumbar puncture, with participants randomized to the gain framed intervention having 67% higher odds of agreeing to be contacted about studies requiring lumbar puncture compared to those randomized to the loss frame.…”
Section: Discussionsupporting
confidence: 89%
“…Recent evidence shows that behavioral nudges could be used to enhance RCT enrollment rates by addressing enrollment barriers [5]. For example, two studies that made use of behavioral nudges in the form of personalization [6] and message framing [7] found them effective in increasing enrollment rates in an RCT of screening of undiagnosed atrial fibrillation and in an RCT designed to test different strategies to increase willingness to undergo research lumbar puncture. Behavioral nudges have been defined as any "aspect of the choice architecture that alters people's behavior in a predictable way without forbidding any options or significantly changing their economic incentives" [8].…”
Section: Introductionmentioning
confidence: 99%
“…We expect some eligible patients to decline participation solely due to the lumbar puncture. This is partly overcome by increasing knowledge of the procedure among patients and hospital staff, since lack of knowledge seems to contribute the most to unwillingness towards lumbar puncture [69].…”
Section: Risk Of Biasmentioning
confidence: 99%
“…36 A recent study involving 851 individuals who had previously indicated unwillingness to be contacted for research involving LP reported that those who received gain-framed video education (i.e., emphasizing the proportion of individuals free of AEs) had 67% higher odds of changing their response compared to those who received loss-framed video education (i.e., emphasizing the portion experiencing AEs), indicating that message framing is important for developing optimal patient education. 109 Reimbursement is a critical "system readiness" barrier. While the expenses of performing LP procedures have been covered-to varying degrees-in the reimbursement frameworks in most countries, overall they tend to be low; the expense of CSF biomarker assays is largely not covered in reimbursement systems.…”
Section: Good Communication Between Physicians and Patients And Theirmentioning
confidence: 99%
“…Informative videos could help improve the knowledge of patients and reduce their fears 36 . A recent study involving 851 individuals who had previously indicated unwillingness to be contacted for research involving LP reported that those who received gain‐framed video education (i.e., emphasizing the proportion of individuals free of AEs) had 67% higher odds of changing their response compared to those who received loss‐framed video education (i.e., emphasizing the portion experiencing AEs), indicating that message framing is important for developing optimal patient education 109 …”
Section: Potential Challenges To Routine Lp In Ad Clinical Practicementioning
confidence: 99%